Abdominal ultrasound activates afferent vagus nerve fibers and induces anti-inflammatory effects - Kotaro Shimoyama; Mamoru Tanida; Jun Aruga; Tomohiro Furusato; Chia-Hsien Wu; Yasuna Nakamura; Daisuke Takahashi; Go Kanzaki; Atsuhiro Maeda; Takao Shioya; Nobuo Tsuboi; Chikara Abe; et al. (Proceedings of the National Academy of Sciences, 2026)
Abdominal ultrasound has emerged as a noninvasive modality with immunomodulatory potential. Although its anti-inflammatory effects have been demonstrated in various disease models, the underlying mechanisms remain unclear. Previous studies suggest that ultrasound promotes anti-inflammatory macrophage polarization via α7 nicotinic acetylcholine receptor (α7nAChR) signaling in the spleen. However, the upstream events initiating this response have not been elucidated. Here, we demonstrate that abdominal ultrasound activates afferent vagal fibers and suppress systemic inflammation. In a murine model of lipopolysaccharide (LPS)-induced endotoxemia, abdominal ultrasound significantly reduced plasma TNF-α levels. This anti-inflammatory effect was attenuated by subdiaphragmatic vagotomy (SDVx) or afferent vagal blockade. Electrophysiological recordings revealed increased cervical vagus nerve activity during ultrasound stimulation, which was eliminated by intraperitoneal lidocaine, confirming activation of abdominal sensory afferents. Furthermore, abdominal ultrasound induced c-Fos expression in the nucleus tractus solitarius (NTS), consistent with central activation via vagal afferent input. These findings provide direct mechanistic evidence that abdominal ultrasound stimulates afferent vagal pathways.